National decision-making for the introduction of new vaccines: A systematic review, 2010–2020. Issue 14 (1st April 2021) - Donadel, Morgane; Panero, Maria Susana; Ametewee, Lynnette; Shefer, Abigail M.
Highlights: Interest in strengthening evidence-based policymaking for vaccines has increased. Burden of disease, vaccine efficacy and safety, impact are used for decision-making. Programmatic, acceptability and equity aspects are not as often considered. Policymakers and advisory groups value interventions based on economic evaluations. Evidence-based recommendation, national governance are enablers for vaccine adoption. Abstract: Background: Competing priorities make using a transparent and evidence-based approach important when deciding to recommend new vaccines. We conducted a literature review to document the processes and frameworks for national decision-making on new vaccine introductions and explored which key features have evolved since 2010. Methods: We searched literature published on policymaking related to vaccine introduction from March 2010 to August 2020 in six databases. We screened articles for eligibility with the following exclusion criteria: non-human or hypothetical vaccines, the sole focus on economic evaluation or decision to adopt rather than policy decision-making. We employed nine broad categories of criteria from the 2012 review for categorization and abstracted data on the country, income level, vaccine, and other relevant criteria. Results: Of the 3808 unique references screened, 116 met eligibility criteria and were classified as: a) framework of vaccine adoption decision-making (27), b) studies that analyse empirical data on or examples of vaccine adoption decision-making (45), c) theoretical and empirical articles that provide insights into the vaccine policymaking process (44 + 17 already included in the previous categories). Commonly reported criteria for decision-making were the burden of disease; vaccine efficacy/effectiveness, safety; impact on health and non-health outcomes; economic evaluation and cost-effectiveness of alternative interventions. Programmatic and acceptability aspects were not as often considered. Most (50; 82%) of the 61 articles describing the process of vaccine introduction policymaking highlighted the role of country, regional, or global evidence-informed recommendations and a robust national governance as enabling factors for vaccine adoption. Conclusions: The literature on vaccine adoption decision-making has expanded since 2010. We found that policymakers and expert advisory committee members (e.g., National Immunization Technical Advisory Group [NITAG]) increasingly value the interventions based on economic evaluations. The results of this review could guide discussions on evidence-informed immunization decision-making among country, sub-regional, and regional stakeholders.